ORGANIZATIONAL COMMUNICATION DYNAMICS IN THE PROCESS OF INTEGRATED INFORMATION SYSTEM IN MUHAMMADIYAH HEALTHCARE CHARITY VENTURE - Rahmawati, Wuri; Rasyid, Erwin (Universitas Muhammadiyah Yogyakarta, 2020)
As a progressing Islamic movement and one of the most prominent Islamic organizations, Muhammadiyah does not only focus on the religious field but also charity ventures in the fields of education, social, and health. Muhammadiyah's potential in developing its charity venture in the health sector is enormous. This study aims to analyze the dynamics of organizational communication in the process of coordinating the integration of the Muhammadiyah health information system. This qualitative research used a case study approach and in-depth interviews, observation, and archival documents, as the data collection technique. This research showed that the integration of health information systems in Muhammadiyah is challenging to realize due to the high potential of the sectoral ego in the process of managing the Muhammadiyah Healthcare Charity Venture (AUMKES). Supervising Council of General Wellbeing (MPKU) as an assembly responsible for planning, organizing, coordinating, and supervising the management of the health sector in Muhammadiyah needs to strengthen its capacity, especially in the area of organizational communication management. This is because MPKU PPM has not had enough power and legitimacy in uniting the perceptions of each RSMA manager.